Simulation and experimental validation of modular multilevel converters capable of producing arbitrary voltage levels using the space vector modulation method - Cuong, Tran Hung; Hieu, Pham Chi; Phuong, Pham Viet (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Modular multilevel converters (MMC) used forDC-AC energy conversion are becoming popular to connect distributed energy systems to the power systems. There are many modulation methods that can be applied to the MMC. The space vector modulation (SVM) method can produce a maximum number of levels, i.e., 2N+1, in which N is the number of sub- modules (SMs) per branch of the MMC. The SVM method can generate rules to apply to MMCs with any number of levels. The goal of this proposal is to easily expand the number of voltage levels of the MMC when necessary while still ensuring the quality requirements of the system. The proposed SVM method only selects the three nearest vectors to generate optimal transition states, therefore making the computations simpler and more efficient. This has reduced the computational load when compared to the previously applied SVM methods. This advantage ensures an optimal switching process and harmonic quality which will significantly improve the effectiveness of the proposed method was demonstrated through simulations on MATLAB/Simulink and experimental tests on 13-levels voltage MMC converter system using a 309 field-programmable gate array (FPGA) kit.